Predicting The Mortality And Need Of Icu Admission By Using Various Scoring System In Patient Present With Hematemesis In Emergency Department. (Indian Journal of Applied-Basic Medical Sciences, 2021)
BACKGROUNG: An overall annual incidence of acute upper gastrointestinal haemorrhage  has been estimated to be 40-150 per 1,00,000 populations (1,2), leads to annual hospital  admission rate of approximately 100 per 1,00,000 hospital admissions, and has significant  associated morbidity and mortality, especially in the elderly. Gastrointestinal bleeding, which  is most commonly arises from mucosal erosive disease accounts for up to 20,000 deaths  annually.  Various risk scoring systems have been recently developed to predict clinical Outcomes and  need of ICU admission in patients with upper gastrointestinal bleeding (UGIB) or hematemesis.  The two commonly used scoring systems include full Rockall score (RS) and the Glasgow Blatchford score (GBS). MATERIAL AND METHOD: An observational, study was conducted on 50 patients with  obvious symptoms of UGIB in the emergency department of SVPIMSR, Ahmedabad. full  Rockall score (RS) and the Glasgow-Blatchford score (GBS)were calculated. Data was  collected from hospital iHiS system and analysed in epi info (version 7.3.2.1) CDC software.  P
Keywords: Hemetemesis; Emergency; Mortality